2020
DOI: 10.3390/jmse8080581
|View full text |Cite
|
Sign up to set email alerts
|

Relative Influence of Environmental Factors on Biodiversity and Behavioural Traits of a Rare Mesopelagic Fish, Trachipterus trachypterus (Gmelin, 1789), in a Continental Shelf Front of the Mediterranean Sea

Abstract: Coastal environments can be influenced by water body masses with particular physical, chemical, and biological properties that create favourable conditions for the development of unique planktonic communities. In this study, we investigated a continental shelf front at Ponza Island (Tyrrhenian Sea) and discussed its diversity and complexity in relation to major environmental parameters. Moon phase and current direction were found to play a significant role in shaping species abundance and behaviour. During in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…Recently, FALSONE et al (2017) estimated an age of 11 years on a specimen of 876 mm TL. For this reason, it would be useful to collect and analyse more & VOLTINA 2006;CORTES et al, 1995;FARIAS et al, 2010;LIPEJ et al, 2018;MYTILINEOU et al, 2013;MACALI et al, 2020;Zu cristatus: TOR-TONESE,1958;IBAÑEZ, 1974;ECKMAYER, 1982;ROIG & DEMESTRE,1982;Scott, 1984;Heemstra e Kannemeyer, 1984;Bianco et al, 2006;Psomadakis et al, 2007;DULCIC et al, 2014;FALSONE et al, 2017;ANGULO & SANCHEZ., 2017;MOHAN et al, 2011;FITCH., 1964;GARCIA-BARCELONA et al, 2014;ZENETOS et al, 2015). Moreover, a single record was collected from data obtained by a social network.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, FALSONE et al (2017) estimated an age of 11 years on a specimen of 876 mm TL. For this reason, it would be useful to collect and analyse more & VOLTINA 2006;CORTES et al, 1995;FARIAS et al, 2010;LIPEJ et al, 2018;MYTILINEOU et al, 2013;MACALI et al, 2020;Zu cristatus: TOR-TONESE,1958;IBAÑEZ, 1974;ECKMAYER, 1982;ROIG & DEMESTRE,1982;Scott, 1984;Heemstra e Kannemeyer, 1984;Bianco et al, 2006;Psomadakis et al, 2007;DULCIC et al, 2014;FALSONE et al, 2017;ANGULO & SANCHEZ., 2017;MOHAN et al, 2011;FITCH., 1964;GARCIA-BARCELONA et al, 2014;ZENETOS et al, 2015). Moreover, a single record was collected from data obtained by a social network.…”
Section: Resultsmentioning
confidence: 99%
“…Juvenile Trachipterus trachypterus were observed in situ by Macali et al (2020) in the upper 10 m of water during nighttime SCUBA dives near an upwelling on the Mediterranean coast of Italy. These individuals were observed to orient vertically, and upon recognition of potential predators (the divers), the fish would orient with their heads up and their elongate pelvic and caudal-fin rays extended.…”
Section: Morphology Of Juvenilesmentioning
confidence: 99%
“…These individuals were observed to orient vertically, and upon recognition of potential predators (the divers), the fish would orient with their heads up and their elongate pelvic and caudal-fin rays extended. Periodic, quick flicking of these fins was hypothesized by Macali et al (2020) to mimic jellyfishes. From video from a submersible, Mortiz et al (2015) also observed a juvenile maintaining a vertical orientation and using undulation of its dorsal fin for locomotion.…”
Section: Morphology Of Juvenilesmentioning
confidence: 99%
See 1 more Smart Citation
“…This special edition is intended to be a contribution to the knowledge of several aspects of fish biology and ecology: coastal fish diversity, coastal fisheries and commercial species, biological invasions process and non-indigenous species, interactions between fish and their environment, ethology, bioaccumulation and reproduction [1][2][3][4][5][6][7][8][9][10][11][12]. I hope this special issue will be helpful for all marine biologists involved in studies on fish biology and ecology.…”
mentioning
confidence: 99%